The adoption of law on marital rape in Malaysia / Aimi Shazwani Yaakob...[et al.] - Yaakob, Aimi Shazwani; Ismail, NurSyahirah; Ramlee, Nur Syazwani; Sayed Abdul Aziz, Sharifah Raudhah (2009)
This research traces the status and significant of marital rape to be applied in our country, focusing on the suitability of the adoption of the marital rape since Malaysia is not adopting this law because most Malaysian are Muslim and it is against the Syariah Law. Comparison between various countries was made in constituting an act as an offence of marital rape. As in Islam, once marriage's contract was made, as implied consent has been given to a husband for sexual intercourse but it does not constitutes the wife is the property to the husband and the husband cannot abuse the wife since religion does not condone violence. In Malaysia, only the Penal Code deals with criminal offences which include rape however marital rape was never regarded as an offence. Malaysia has yet to follow the landmark decisions in the English case R v R [1992] 1 AC 599. Since it is hard to prove marital rape cases, Malaysia has interpret the marital rape issue in their own way by having the provision under Section 375 A of the Penal Code where the wife must prove to the court of law that the husband caused hurt or fear of death or hurt to the wife or somebody else. Until today, there is no local case that specifically deals with marital rape per se as a form of abuse probably due to the reluctant express recognition of marital rape in the Penal Code. Thus, this research will consider the suitability of the adoption of the law on marital rape to be applied to Malaysian law.